Effects of the eccentricity of the primaries in powered Swing-By maneuvers - Ferreira, Alessandra F.S.; Prado, Antônio F.B.A.; Winter, Othon C. [UNESP]; Santos, Denilson P.S. [UNESP] (Elsevier, 2017)
The present paper studies the powered Swing-By maneuver when performed in an elliptical system of primaries. It means that there is a spacecraft travelling in a system governed by the gravity fields of two bodies that are in elliptical orbits around their center of mass. The paper particularly analyzes the effects of the parameters relative to the Swing-By (Vinf-,rp,ψ), the orbit of the secondary body around the primary one (e,ν) and the elements that specify the impulse applied (δV,α) to the spacecraft. The impulse is applied when the spacecraft passes by the periapsis of its orbit around the body, where it performs the Swing-By, with different magnitudes and directions. The inclusion of the orbital eccentricity of the primaries in this problem makes it closer to reality, considering that there are many known systems with eccentricities different from zero. In particular, there are several moons in the Solar System which orbits are not circular, as well as some smaller bodies, like the dwarf planet Haumea and its moons, which have eccentricities of 0.25 or even larger. The behavior of the energy variation of the spacecraft is shown in details, as well as the cases where captures and collisions occur. The results show the conditions that optimize this maneuver, according to some given parameters, and how much can be obtained in terms of gains or losses of energy using the best conditions found by the algorithm developed here.
Keywords: Astrodynamics; ERTBP; Impulsive maneuvers; Powered Swing-By maneuvers; Spacecraft trajectories